Kenangan Jalan Kenanga : koleksi esei Dato' Razali Ismail - Sharif Putera (Kuala Lumpur, Malaysia : Dewan Bahasa dan Pustaka, 2016)
Collection of essays of Dato' Razali Ismail on education and Malay literature
1. Pendidikan -- 2. Sastera, budaya dan pembangunan insan
Includes bibliographical references (pages 297-301) and index
Keywords: Drama in education; Drama in education -- Malaysia; Education -- Malaysia; Government publications -- Malaysia; Malay essays; Malay literature -- History and criticism; Teachers -- Training of -- Malaysia